2013
DOI: 10.1021/jp409887t
|View full text |Cite
|
Sign up to set email alerts
|

5-Methylation of Cytosine in CG:CG Base-Pair Steps: A Physicochemical Mechanism for the Epigenetic Control of DNA Nanomechanics

Abstract: Van der Waals density functional theory is integrated with analysis of a non-redundant set of protein-DNA crystal structures from the Nucleic Acid Database to study the stacking energetics of CG:CG base-pair steps, specifically the role of cytosine 5-methylation. Principal component analysis of the steps reveals the dominant collective motions to correspond to a tensile ‘opening’ mode and two shear ‘sliding’ and ‘tearing’ modes in the orthogonal plane. The stacking interactions of the methyl groups globally in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…Other modifications induce different patterns of structural change: for the central base pair these changes are typically smaller than for methylation, but for base pair steps much larger changes are found in some parameters. Most notable of these are slide, which changes by over 3 Å and roll (up to 17°) in the 3´ direction, in a similar way to that reported previously for smaller systems 17, 18 . Other parameters such as the width of the DNA strand, measured as the distance between C1´ nuclei, and virtual angles λ Y and λ R , which describe the pivoting of complementary bases in the base-pair plane, vary only slightly from the idealised values for B-DNA.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Other modifications induce different patterns of structural change: for the central base pair these changes are typically smaller than for methylation, but for base pair steps much larger changes are found in some parameters. Most notable of these are slide, which changes by over 3 Å and roll (up to 17°) in the 3´ direction, in a similar way to that reported previously for smaller systems 17, 18 . Other parameters such as the width of the DNA strand, measured as the distance between C1´ nuclei, and virtual angles λ Y and λ R , which describe the pivoting of complementary bases in the base-pair plane, vary only slightly from the idealised values for B-DNA.…”
Section: Resultssupporting
confidence: 86%
“…Regarding epigenetic modifications in particular, Acosta-Silva et al 17 showed in this manner that methylation enhances stacking interactions, and can produce local distortions in base-pair step parameters, most notably slide. Yusufaly et al used similar calculations to show that methylation can induce over-twisting as well as softer modes for distortion from the global energy minimum 18 . We recently employed classical mechanics to examine not only the structure but also the flexibility of different DNA sequences with methyl and hydroxymethyl substituents 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis is performed on a non-redundant dataset of protein-bound DNA obtained from the Nucleic Acid Database 31 and reported in a previous publication 11 . From this dataset, a fourteen-parameter data vector is generated that characterizes the atomic configuration of the model complex illustrated in Figure 3.…”
Section: Principal Component Analysis Of the Sugar-phosphate Backbonementioning
confidence: 99%
“…168 DNA methylation increases the rigidity of the chromatin structure and disfavours the positioning of nucleosomes on DNA. 169,170 Splicing entropy. RNA maturation process includes the assembly of gene products through splicing machinery.…”
Section: Intracellularmentioning
confidence: 99%